2007
DOI: 10.1159/000111800
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Assessment of Young Women’s Voices as a Function of Oral Contraceptive Use

Abstract: Objective: To examine possible differences in glottal airflow parameters according to oral contraceptive (OC) use. Subjects and Methods: The participants included 16 women, 20–24 years of age. Eight women were taking a triphasic OC; the remaining 8 women were not taking any form of oral contraception (NOC). All participants were recorded on days 7 and 14 of their menstrual cycle. Three repetitions of the sustained vowel /a/ were obtained using a circumferentially vented respiratory face mask connected to a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Prior research has demonstrated no conclusive relationship between airflow rates, menstrual cycle phase, and OC use. 26 Thus, for this participant, the changes in hormonal levels with OC use did not appear to affect the stiffness of her vocal folds. It was assumed that the observed changes in speech acoustics would result in greater stability of these measures across the phases of the menstrual cycle.…”
Section: Richard J Morris Et Almentioning
confidence: 72%
“…Prior research has demonstrated no conclusive relationship between airflow rates, menstrual cycle phase, and OC use. 26 Thus, for this participant, the changes in hormonal levels with OC use did not appear to affect the stiffness of her vocal folds. It was assumed that the observed changes in speech acoustics would result in greater stability of these measures across the phases of the menstrual cycle.…”
Section: Richard J Morris Et Almentioning
confidence: 72%